Early lactation failure and formula adoption after elective caesarean delivery: cohort study. Issue 1 (19th April 2012) - Zanardo, Vincenzo; Pigozzo, Anna; Wainer, Gary; Marchesoni, Diego; Gasparoni, Antonella; Di Fabio, Sandra; Cavallin, Francesco; Giustardi, Arturo; Trevisanuto, Daniele
Abstract : Objective: To investigate the effects of elective primary and elective repeat caesarean deliveries on lactation at hospital discharge. Design: Cohort study. Setting: Four Italian teaching hospitals – Padua, Brescia, L'Aquila and Udine. Interventions: Deliveries were classified as vaginal, elective caesarean (primary and repeat) or emergency caesarean. A total of 2296 (24.7%) infants born by caesarean section (CS), 816 of which (35.5%) classified as primary elective CS and 796 (34.7%) as repeat elective CS, were studied. Moreover, 30.2% of the elective CS deliveries took place before 39 weeks. Main outcome measures: Feeding modalities at discharge: formula, complementary and breastfeeding. Results: At discharge, 6.9% of the vaginal delivery mothers, 8.3% of the emergency CS mothers, 18.6% of the elective CS mothers, 23.3% of the primary CS mothers and 13.9% of the repeat CS mothers were using infant formula exclusively. Multivariate analysis (OR; 95% CI) identified primary elective delivery (3.74; 3.0 to 4.60), lower gestational age (1.16; 1.10 to 1.23), and place L'Aquila versus Udine (1.42; 1.01 to 2.09) and of Brescia versus Udine hospitals (6.16; 4.53 to 8.37) as independent predictors of formula feeding at discharge. Conclusions: These findings provide new information about the risks of breastfeeding failure connected to elective CS delivery, particularly if primary and scheduled before 39 weeks of gestation.